# Solve the following trigonometrical equation when the angle α is acute - 2sinαtanα + 1 = tanα + 2sinα

2
by gunsingh99

2015-04-16T12:08:05+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Our first step is to rearrange the equation and factor.

Next use zero product property and get
or
or

Since we want acute
or

So the solutions are
2015-04-16T13:13:45+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
2sinαtanα +1= tanα +2sinα
2sinαtanα  -2 sinα +1 - tanα=0
2sinα(tanα -1) -1( tanα -1) =0
(2sinα-1)(tanα -1)=0
either (2sinα-1) =0 or (tanα-1)=0
If 2sinα-1=0      ,  if tanα-1=0
2sinα=1          ,      tanα=1
sinα=1/2        ,    tanα=tanπ/4
sinα= sinπ/6           , α=π/4
α=π/6  ,if α is acute

thankyou ,Rational bhai